HUBUNGAN INTENSITAS PAPARAN INFORMASI PENYULUHAN IMUNISASI DENGAN TINGKAT PENGETAHUAN IBU DALAM PEMBERIAN IMUNISASI DASAR LENGKAP PADA BALITA DI DUSUN MENTIGI KABUPATEN LOMBOK UTARA - Aulia Rinjani Lestari; Ayu Anulus; Sulatun Hidayati; Dewi Utary (Yayasan Nusantara Hasana Berdikari, 2023)
Immunization is one way to prevent the occurrence of certain diseases, besides being useful, immunization also provides side effects known as Post-Immunization Follow-up Events (AEFI). Based on the 2013 Riskesdas it was found that out of 91.3% of children in Indonesia who had been immunized, there were 33.4% who had experienced AEFI. It is necessary to educate the community, especially mothers, to understand the importance of providing complete basic immunization to children.Aims of this research to determine the relationship between the intensity of information exposure and the level of knowledge of mothers about basic immunization in children in Mentigi Hamlet, Pemenang District, North Lombok Regency. This research is a quantitative analytic observational study with a cross sectional study design. The sample in this study was mothers in Mentigi Hamlet, Pemenang District, North Lombok Regency in 2023, totaling 99 people. The sampling method in this study used purposive sampling. The dependent variable in this study was the mother's knowledge of complete basic immunization and the independent variable was the intensity of counseling. The method used in data collection is a questionnaire. Data analysis using chi square. The results of this study showed that the highest intensity of counseling was in the poor category of 63 people (63.64%) while the mother's level of knowledge about complete basic immunization was highest in the good category of 59 people (59.0%). The results of the analysis using the chi square test obtained a p-value of 0.005 there was a significant relationship between the intensity of counseling and the level of knowledge of mothers about basic immunization in children in Mentigi Hamlet, Pemenang District, North Lombok Regency. There is a relationship between the intensity of information exposure and the level of knowledge of mothers about basic immunization in children in Mentigi Hamlet, Pemenang District, North Lombok Regency.